Withholding the Introduction of Anti‐Epidermal Growth Factor Receptor: Impact on Outcomes in RAS Wild‐Type Metastatic Colorectal Tumors: A Multicenter AGEO Study (the WAIT or ACT Study). (2nd October 2019) - Palmieri, Lola‐Jade; Mineur, Laurent; Tougeron, David; Rousseau, Benoît; Granger, Victoire; Gornet, Jean‐Marc; Smith, Denis; Lievre, Astrid; Galais, Marie‐Pierre; Doat, Solene; Pernot, Simon; Bignon‐Bretagne, Anne‐Laure; et al.
Abstract: Background: Patients with RAS wild‐type (WT) nonresectable metastatic colorectal cancer (mCRC) may receive either bevacizumab or an anti‐epidermal growth factor receptor (EGFR) combined with first‐line, 5‐fluorouracil‐based chemotherapy. Without the RAS status information, the oncologist can either start chemotherapy with bevacizumab or wait for the introduction of the anti‐EGFR. Our objective was to compare both strategies in a routine practice setting. Materials and Methods: This multicenter, retrospective, propensity score–weighted study included patients with a RAS WT nonresectable mCRC, treated between 2013 and 2016 by a 5‐FU‐based chemotherapy, with either delayed anti‐EGFR or immediate anti‐vascular endothelial growth factor (VEGF). Primary criterion was overall survival (OS). Secondary criteria were progression‐free survival (PFS) and objective response rate (ORR). Results: A total of 262 patients (129 in the anti‐VEGF group and 133 in the anti‐EGFR group) were included. Patients receiving an anti‐VEGF were more often men (68% vs. 56%), with more metastatic sites (>2 sites: 15% vs. 9%). The median delay to obtain the RAS status was 19 days (interquartile range: 13–26). Median OS was not significantly different in the two groups (29 vs. 30.5 months, p = .299), even after weighting on the propensity score (hazard ratio [HR] = 0.86, 95% confidence interval [CI], 0.69–1.08, p = .2024). The delayed introduction of anti‐EGFR was associated with better median PFS (13.8 vs. 11.0 months, p = .0244), even after weighting on the propensity score (HR = 0.74, 95% CI, 0.61–0.90, p = .0024). ORR was significantly higher in the anti‐EGFR group (66.7% vs. 45.6%, p = .0007). Conclusion: Delayed introduction of anti‐EGFR had no deleterious effect on OS, PFS, and ORR, compared with doublet chemotherapy with anti‐VEGF. Implications for Practice: For RAS/RAF wild‐type metastatic colorectal cancer, patients may receive 5‐fluorouracil‐based chemotherapy plus either bevacizumab or an anti‐epidermal growth factor receptor (EGFR). In daily practice, the time to obtain the RAS status might be long enough to consider two options: to start the chemotherapy with bevacizumab, or to start without a targeted therapy and to add the anti‐EGFR at reception of the RAS status. This study found no deleterious effect of the delayed introduction of an anti‐EGFR on survival, compared with the introduction of an anti‐vascular endothelial growth factor from cycle 1. It is possible to wait one or two cycles to introduce the anti‐EGFR while waiting for RAS status. Abstract : More than half of the cases of metastatic colorectal cancer harbor a RAS mutation; however, the time to obtain RAS status might be long enough to consider delayed anti‐EGFR treatment. This article reports on the two main treatment strategies for these cases.